Updated DEGUM Quality Requirements for the Basic Prenatal Screening Ultrasound Examination (DEGUM Level I) between 18 + 0 and 21 + 6 weeks of gestation - Kähler, Christiane; Schramm, Thomas; Bald, Rainer; Gembruch, Ulrich; Merz, Eberhard; Eichhorn, Karl-Heinz (Ultraschall in der Medizin - European Journal of Ultrasound, 2020)
A precondition for the early detection of fetal abnormalities is the high quality of prenatal basic ultrasound (screening examination). The objective of ultrasound screening is the recognition of abnormal fetal growth and fetal anatomical anomalies. The prenatal detection of fetal abnormalities enables detailed prenatal counselling of parents, improved care at birth and potentially a reduction in morbidity and mortality. In the guidelines for maternity care in Germany (“Mutterschaftsrichtlinien”), the performance of basic ultrasound in pregnancy is not clearly defined. The required image documentation includes a few biometric measurements only. Therefore, adherence to a standard technique and the possibility of audit are limited, thus not necessarily resulting in high screening quality. In this update of the DEGUM quality requirements for level I screening ultrasound examination between 18 + 0 and 21 + 6 weeks of gestation, the required parameters, standard planes and required documentation are described in detail. The greater experience of gynecologists in the field of sonographic screening examinations and the use of a modern ultrasound technique allow improvement of the screening quality. This will improve the standard of basic ultrasound screening. Due to the enhanced standard of the DEGUM I examination, more pregnant women may benefit from a detailed ultrasound examination and specialized therapy in DEGUM level II and III centers. The required fetal structures are described in detail. This update of the requirements for level I DEGUM basic ultrasound examination between 18 + 0 and 21 + 6 weeks of gestation goes far beyond the guidelines for maternity care in Germany (the “Mutterschaftsrichtlinien”) thereby elevating standards.Eine hohe Qualität der pränatalen Basisdiagnostik in den Ultraschall-Screeninguntersuchungen ermöglicht eine Steigerung der Qualität der Untersuchung und somit die frühzeitige Erkennung fetaler Störungen. Aufgabe des Screenings ist die Detektion von Hinweiszeichen auf fetale Erkrankungen, Entwicklungsstörungen oder Fehlbildungen. Deren pränatale Diagnose führt in vielen Fällen zu einer Verbesserung der Therapiemöglichkeiten, der Lebensqualität der betroffenen Kinder und Senkung der perinatalen Mortalität und Morbidität. In den deutschen Mutterschaftsrichtlinien sind die Leistungsinhalte der Ultraschall-Screeninguntersuchungen nicht klar definiert. Die geforderte Bilddokumentation umfasst lediglich die Biometrie. Dies erschwert das Erreichen und die Einhaltung einer hohen Qualität sowie die Qualitätskontrolle. In den aktualisierten Empfehlungen für die DEGUM-Stufe-I-Untersuchung zwischen 18 + 0 und 21 + 6 Wochen werden die Inhalte dieser Untersuchung und deren Dokumentation dagegen detailliert beschrieben. Die gestiegene Erfahrung der Untersucherinnen und Untersucher und die Verwendung einer modernen Ultraschalltechnik bereits im Screening ermöglichen eine Steigerung der Qualitätskriterien und somit eine Stärkung der pränatalen Basisdiagnostik. Durch die Erhöhung der Qualität der DEGUM-Stufe-I-Untersuchung können mehr Schwangere von einer gezielten weiterführenden Diagnostik und Therapie in Stufe-II- und -III-Zentren profitieren. Die vorliegenden DEGUM-Empfehlungen entsprechen deshalb wesentlich besser den heutigen Möglichkeiten und Erfordernissen einer Ultraschalluntersuchung im zweiten Trimenon. Sie ermöglichen eine hochwertige Ultraschall-Screeninguntersuchung, die sich durch die genaue Definition der darzustellenden fetalen Strukturen qualitativ und quantitativ von den Mindestanforderungen der derzeit gültigen Mutterschaftsrichtlinien abhebt.
Keywords: prenatal diagnosis; second trimester; level I examination; quality requirements